The Role of Islamic Finance and Banking for Kurdistan in the Next Decade - Ahmet Sekreter (International Journal of Social Sciences & Educational Studies, 2017)
The Kurdistan Regional Government is recognized as a semiautonomous region in northern Iraq. Although Kurdistan is in the Middle East where the region hosts enormous conflicts and uncertainty, it is differentiated in terms of security, stability and democracy. Kurdistan is in the 51st place in oil production and 58th place in natural gas production however it is 9th place in oil-proved reserves and it is in 11th place in natural gas-proved reserves. These statistics put forth that Kurdistan region has a potential to show a great economic growth. Investment opportunities are going to diffuse in many different fields in the short and medium term. All these facts and expectations show that the banking system especially Islamic finance and banking due to the religious perspective of the Muslim community in Kurdistan is going to play a crucial role in the path of the development of the region like in the early stage of the other developing countries. This paper analyses the short history of Kurdistan’s financial system and Islamic banking, current situation, and tries to state challenges and opportunities of Islamic banking and finance in Kurdistan in near future. Since there are very few studies for Kurdistan region this paper will contribute to the literature and future studies.